Back Cover: Characterization of Paramagnetic Reactive Intermediates: Predicting the NMR Spectra of Iron(IV)–Oxo Complexes by DFT (Chem. Eur. J. 37/2015). Issue 37 (7th September 2015) - Borgogno, Andrea; Rastrelli, Federico; Bagno, Alessandro
<x xml:space="preserve">Abstract</x> FeIV complexes and related species, such as FeIVO porphyrins, are investigated as models of biological oxygenases and as catalysts. By comparing experimental proton NMR spectra with those obtained from DFT calculations, A. Borgogno, F. Rastrelli, and A. Bagno show in their Full Paper on page 12960 ff. that the paramagnetism of these species can be exploited to assess the ground spin states. In most cases, the correct spin state can even be predicted by calculations alone; a particularly useful result in the structural elucidation of species with challenging NMR spectra.